Effects of smoking cessation on pulmonary function and quality of life - P. M., Ramesh; M., Saravanan; ., Divya (International Journal of Advances in Medicine, 2018)
Background: Cigarette smoking is a major public health problem and is the most important cause of chronic obstructive pulmonary disease (COPD). This study shows the importance of smoking cessation for improvement in respiratory function and quality of life and brings out the potential usage of pharmacological and behavioural therapy for the same. Methods: This prospective study was conducted on 50 male smokers at Kilpauk Medical College, Chennai. During the treatment only 43 patients were continued till the end of follow up. During the period, varenicline treatment was given for three months as per schedule, regular periodic counselling was given to these patients and followed up for a period of 1 year. Forced expiratory volume at one second (FEV1), COPD assessment test (CAT) scoring, 6 min walk test (6MWD), BODE index, was taken before starting therapy and on 3rd month and at the end of one year of follow-up. All the values obtained were analysed statistically. Results: The mean age of the 43 patients was 44.7±7.34, mean BMI was 22.27±4.24. The mean difference between pre and post treatment scores of CAT, 6MWD and BODE index were found to be statistically significant (p<0.0001). Conclusions: Combined behavioural counseling and pharmacotherapy with varenicline significantly improved the odds of achieving tobacco abstinence in the participants by the end of one year of treatment.